EFFECT OF ROASTING TIME ON CAFFEINE CONTENT IN ARABICA COFFEE BEANS BY ANALYTICAL METHOD HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) - Nurkholifaturrohmah; Perwitasari, Melania; Putri, Intan Kurnia; Beandrade, Maya Uzia (STIKes Mitra Keluarga, 2026)
Introduction : Caffeine is an alkaloid compound that can be harmful to health if consumed in excess. One factor believed to influence caffeine levels in coffee is the processing method, particularly the roasting time. Therefore, this study focuses on the effect of varying roasting times on caffeine levels in coffee. Method: This study was conducted as a quantitative experimental study. Arabica coffee beans were roasted at 220 C for 10 minutes, 15 minutes, and 20 minutes, with green coffee beans (unroasted) serving as a control. The samples were analyzed by High-Performance Liquid Chromatography (HPLC) using a mobile phase of distilled water:methanol (75:25), C18 column, a flow rate of 1 mL/min, and lamda max 273 nm. Caffeine content was determined using a verified HPLC analysis method. Result: The moisture content of green coffee beans roasted for 10 minutes, 15 minutes, and 20 minutes was 9.04, 1.93, 1.63, and 1.44, respectively. Caffeine content analysis was performed using a validated HPLC method. The average caffeine content of green coffee beans at roasting times of 10 minutes, 15 minutes, and 20 minutes, respectively, was 0.0065, 0.0096, 0.0088, and 0.0074. A significance value of 0.000 (p < 0.05) indicates a significant difference in caffeine content among the treatments, suggesting that roasting time affects the caffeine content in coffee. Conclusion: Differences in roasting time have a significant effect on the caffeine content of Arabica coffee, with changes showing an increase during the early stages of roasting, followed by a decrease as roasting progresses.